Targeting CDK9 by wogonin and related natural flavones potentiates the anti-cancer efficacy of the Bcl-2 family inhibitor ABT-263 - Polier, Gernot; Giaisi, Marco; Köhler, Rebecca; Müller, Wolfgang W.; Lutz, Christoph; Buß, Eike Christian; Krammer, Peter H.; Li-Weber, Min (International journal of cancer, 2015)
Tumor initiation, progression and resistance to therapies are tightly associated with over-expression of anti-apoptotic proteins Bcl-2, Bcl-xL, Bcl-w and Mcl-1. ABT-263 (Navitoclax), an orally bio-available small-molecule mimetic of the Bcl-2 homology domain 3, inhibits Bcl-2, Bcl-xL, and Bcl-w and has shown anti-cancer effects mainly on lymphomas and lymphocytic leukemia. Despite promising results obtained from the clinical trials, the use of ABT-263 in patients is dose-limited due to causing thrombocytopenia via inhibition of Bcl-xL in platelets. ABT-199 specifically inhibits Bcl-2; however, its use is limited to tumors over-expressing only Bcl-2. Besides, many tumors resist treatment due to high levels of Mcl-1 expression or develop resistance via up-regulation of Mcl-1 during long-term exposure. These obstacles highlight the demand to improve the ABT-263-based therapy. In this study, we show that anti-cancer flavones, e.g., wogonin, baicalein, apigenin, chrysin and luteolin enhance ABT-263-induced apoptosis in different cancer cell lines and in primary AML and ALL cells by down-regulation of Mcl-1 expression. Importantly, wogonin does not enhance the toxicity of ABT-263 to proliferating normal T cells and thrombocytes. Wogonin also potentiates the lethality of ABT-263 in cancer cells which have acquired resistance to ABT-263. Furthermore, we show that combination of wogonin with ABT-263 promotes in vivo tumor regression in a human T-cell leukemia xenograft mouse model. Our study demonstrates that wogonin (and related flavones) reduce the effective dose of ABT-263 thereby possibly decreasing the risk of adverse side effects.
Online 4 June 2014
Gesehen am 22.07.2020